Differentiation in populations of the apple scab fungus Venturia inaequalis on cultivars in a mixed orchard remain over time. (13th January 2016) - Passey, T. A. J.; Shaw, M. W.; Xu, X.‐M.
Abstract : The ascomycete Venturia inaequalis causes annual epidemics of apple scab worldwide. Scab development is reduced in mixed cultivar orchards compared with monocultures. In order to use mixtures in commercial production, how the population of scab changes in a mixed orchard needs to be understood, together with how likely a super race, with virulence factors overcoming multiple resistance factors in the mixed orchard, is to emerge and become dominant. This study used simple sequence repeat (SSR) markers to investigate the temporal change of scab populations in two mixed cultivar orchards in the UK to infer the likelihood of emergence of a scab super race. There were no significant differences between the populations at the two sampling times (6 or 7 years apart) in either of the two mixed orchards. In one of the orchards, apple scab populations on different cultivars were significantly different and the differences did not diminish over time. These results suggest that it is not inevitable that a super race of V. inaequalis will become dominant during the lifetime of a commercial apple orchard.